2006
DOI: 10.1111/j.1365-2222.2006.02470.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of fluvastatin on cytokine and chemokine production by peripheral blood mononuclear cells in patients with allergic asthma

Abstract: Fluvastatin has inhibitory effects on cytokine and chemokine production, and thus might be used as a potential therapeutic agent in severe asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 29 publications
0
36
0
2
Order By: Relevance
“…Statins also modulate monocyte-macrophage function and inflammatory responses (33,34), consistent with our finding of reduced BALF macrophage counts ( Figure 1D). Peripheral blood mononuclear cells from patients with asthma display reduced chemokine and cytokine production after fluvastatin treatment (35), antiinflammatory effects that may be mediated via GGPP depletion (Scheme 1) (36). Clearly, there is mechanistic precedence that supports the central role of the MA pathway in modulating the simvastatin inhibition of OVAinduced airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Statins also modulate monocyte-macrophage function and inflammatory responses (33,34), consistent with our finding of reduced BALF macrophage counts ( Figure 1D). Peripheral blood mononuclear cells from patients with asthma display reduced chemokine and cytokine production after fluvastatin treatment (35), antiinflammatory effects that may be mediated via GGPP depletion (Scheme 1) (36). Clearly, there is mechanistic precedence that supports the central role of the MA pathway in modulating the simvastatin inhibition of OVAinduced airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…26 The benefits of statin medications for asthma were thought to be dose-dependent, which may account for the apparently conflicting data in murine studies that tested the effects of statins at various doses. 18,25 A low dose of statins may inhibit chemotaxis of type 1 helper T cells, which cause proliferation and aggregation, whereas large doses of statins may inhibit cell death of dendritic cells that differentiate to T h 2 cells. 13,25 These hypotheses have been tested and verified in mice.…”
Section: Journal Of International Medical Research 41(2)mentioning
confidence: 99%
“…27 In contrast, it has been argued that although asthma may be controlled by ICS, the long-term use of ICS carries the risk of side-effects such as adrenal suppression, growth inhibition, and osteoporosis. 18 Statins may help improve the results of long-term ICS treatment and prevent the above-mentioned side-effects. An experiment was undertaken to verify whether statins could prevent and improve airway remodelling, according to regulation of the proliferation of goblet cells and the production of profibrogenic mediators; the authors concluded that statins should be used for asthma.…”
Section: Journal Of International Medical Research 41(2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical in vitro and in vivo studies, including experimental models of allergic [146] and tobacco-smokeinduced lung inflammation [147] found that statins reduce components of airway inflammation potentially relevant to the pathogenesis of asthma and smoke-induced airway diseases. Statins may also restore corticosteroid sensitivity in asthma [148,149]. In smokers with asthma the effects of atorvastatin alone and in combination with inhaled corticosteroid 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 27 was investigated on the ability to suppress the concentration of a range of cytokines, chemokines and growth factors in sputum [150,151] in patients with stable COPD [152].…”
Section: Statinsmentioning
confidence: 99%